The Role of Morphine in Animal Models of Human Cancer: Does Morphine Promote or Inhibit the Tumor Growth?. (27th August 2013) - Bimonte, Sabrina; Barbieri, Antonio; Palma, Giuseppe; Arra, Claudio
Abstract : Morphine, a highly potent analgesic agent, is widely used to relieve pain and suffering of patients with cancer. Additionally, it has been reported that morphine is important in the regulation of cancerous tissue. Morphine relieves pain by acting directly on the central nervous system, although its activities on peripheral tissues are responsible for many adverse side effects. For these reasons, it is very important also to understand the role of morphine in cancer treatment. The published literature reporting the effect of morphine on tumor growth presents some discrepancies, with reports suggesting that morphine may either promote or inhibit the tumor growth. It has been also demonstrated that morphine modulates angiogenesis which is important for primary tumour growth, invasiveness, and the development of metastasis. This review will focus on the latest findings on the role of morphine in the regulation of cancer cell growth and angiogenesis.